2021
DOI: 10.1186/s12873-021-00428-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute cannabis intoxication in the emergency department: the effect of legalization

Abstract: Background On October 17, 2018, the Cannabis Act decriminalized the recreational use of cannabis in Canada. This study seeks to determine how legalization of cannabis has impacted emergency department (ED) visits for acute cannabis intoxication. Methods We conducted a retrospective chart review at an academic ED in Hamilton, Ontario. We assessed all visits with a cannabis-related ICD-10 discharge code 6 months before and after legalization (October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 14 publications
0
36
3
Order By: Relevance
“…edibles and commercialization), we found evidence of an immediate increase in cannabisrelated ED visits; however, no studies including ours have been able to isolate the Phase 2 effect from the COVID-19 effects that coincided with Phase 2. Only one study from Hamilton, Ontario contradicted our results: they found that there was no change in the rate of cannabis-related ED visits following legalization (20), but the authors only examined a single hospital, and did not measure level and trend changes.…”
Section: Discussioncontrasting
confidence: 82%
“…edibles and commercialization), we found evidence of an immediate increase in cannabisrelated ED visits; however, no studies including ours have been able to isolate the Phase 2 effect from the COVID-19 effects that coincided with Phase 2. Only one study from Hamilton, Ontario contradicted our results: they found that there was no change in the rate of cannabis-related ED visits following legalization (20), but the authors only examined a single hospital, and did not measure level and trend changes.…”
Section: Discussioncontrasting
confidence: 82%
“…Studies and reports examining changes in cannabis use and harms in the immediate period following legalization have generally reported no or modest increases in self-reported cannabis use and cannabisattributable health-care visits [5][6][7][8][9]. However, most of these studies have conceptualized legalization as a binary and short-term event [5,[8][9][10] which fails to consider the substantial and continuing expansion of the legal cannabis market (in both cannabis stores and sales) over time in jurisdictions throughout Canada [11,12]. A large body of evidence from other legal commercialized substances (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Though cannabis consists of various cannabinoid compositions, the primary psychoactive compound is Δ9-Tetrahydrocannabinol (THC) that influences the Peripheral Nervous system (PNS) and the Central Nervous System (CNS) through cannabinoid 1 (CB1) receptor agonist together with other body organs [3,7,8]. This receptor is part of the endogenous cannabinoid system, consisting of the metabolism of the endocannabinoids, reuptake, the biochemical machinery for synthesis, endogenous ligands, and CB2 receptors [3].…”
Section: Cannabis Endogenous Effect and Adverse Outcomesmentioning
confidence: 99%
“…Considering that the widespread distribution of CB1 receptors in the CNS, THC creates a wide range of dose-dependent, acute psychotropic impacts, such as feeling high "euphoria" and relaxation, which is thought to be the major reason for cannabis consumption [3]. Moreover, THC has been used recreationally through various forms: vaporized, smoked, orally ingested, or even topically applied [7]. Acute cannabis intoxication includes both physical (cognitive impairment, tachycardia, conjunctival injection, and shortterm memory tasks) and psychiatric effects (relaxation, euphoria, loss of inhibition, and time distortion) [7].…”
Section: Cannabis Endogenous Effect and Adverse Outcomesmentioning
confidence: 99%
See 1 more Smart Citation